The State of Service Related Competences in Montenegro - Jelena Šaković Jovanović; Sanja Peković; Branko Bošković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
European business sector pays more increasing attention ever to competences, such as the sense of initiative and Service related skills. Social, Personal, and Organizational Competences are becoming competitive factors in the service economy, even though these competences are mainly being acquired in informal contexts. Still, there are no opportunities to acquire these competences at most universities. It was the main reason for conducting research and developing the Erasmus+ project E-VIVA project, with the aim to develop a learning approach for Service Related Competences in Higher Education. The University of Montenegro and the University of Donja Gorica are involved as partners on the E-VIVA project in the research of the state of the art of Service Related Competences in Montenegro. Accordingly, the two institutions performed joint research in the field through three instruments: desk research, online questionnaires, and an interview. Target groups for the research were: students, HEI, enterprises, administration, Chamber of Commerce. In this paper, the results of the research are presented, with a special focus on results obtained in online questionnaires. The main reason for that research is to evaluate a current state of Service related competences in Montenegro and to develop a model for the improvement of these competences in Higher education, in order to improve the employability of future graduates.
Keywords: L26; 330; entrepreneurship; innovation; desk research; questionnaire